Standardization of Prothrombin Time/International Normalized Ratio (PT/INR). (26th September 2020) - Dorgalaleh, Akbar; Favaloro, Emmanuel J.; Bahraini, Mehran; Rad, Fariba
Abstract: The prothrombin time (PT) represents the most commonly used coagulation test in clinical laboratories. The PT is mathematically converted to the international normalized ratio (INR) for use in monitoring anticoagulant therapy with vitamin K antagonists such as warfarin in order to provide test results that are adjusted for thromboplastin and instrument used. The INR is created using two major PT 'correction factors', namely the mean normal PT (MNPT) and the international sensitivity index (ISI). Manufacturers of reagents and coagulometers have made some efforts to harmonizing INRs, for example, by tailoring reagents to specific coagulometers and provide associated ISI values. Thus, two types of ISIs may be generated, with one being a 'general' or 'generic' ISI and others being reagent/coagulometer‐specific ISI values. Although these play a crucial role in improving INR results between laboratories, these laboratories reported INR values are known to still differ, even when laboratories use the same thromboplastin reagent and coagulometer. Moreover, ISI values for a specific thromboplastin can vary among different models of coagulometers from a manufacturer using the same method for clot identification. All these factors can be sources of error for INR reporting, which in turn can significantly affect patient management. In this narrative review, we provide some guidance to appropriate ISI verification/validation, which may help decrease the variability in cross laboratory reporting of INRs.